2022
DOI: 10.1177/13524585211061343
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G immune response to SARS-CoV-2 vaccination in people living with multiple sclerosis within Multiple Sclerosis Partners Advancing Technology and Health Solutions

Abstract: Background: The impact of multiple sclerosis (MS) disease-modifying therapies (DMTs) on SARS-CoV-2 vaccination response is uncertain. Methods: Post-SARS-CoV-2 vaccination blood samples across multiple DMTs were tested for SARS-CoV-2 immunoglobulin G (IgG) response. Results: Three hundred twenty-two people with MS were included; 91.9% received an mRNA vaccine. Post-vaccination reactive IgG rates (IgG index > 1) were 40% for anti-CD20 (32/80 patients); 41% for sphingosine 1-phosphate receptor modulators (S1PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 16 publications
1
28
0
1
Order By: Relevance
“…As MS is an immune-mediated disease and DMTs alter or suppress the immune system in different ways, many recent studies have focused on the immunological responses after SARS-CoV-2 infection or vaccination. Overall, most pwMS present an immunological response after SARS-CoV-2 infection (humoral response: 76.8%-83.4%; cellular response: 59.5%) [11][12][13] or vaccination (humoral response: 74.4%-86.8%; cellular response: 62%-84.4%) [14][15][16][17] regardless of their treatment. However, it is clear by now that anti-CD20 therapies and sphingosine-1-phosphate receptor modulator (SP1RM) therapies decrease these responses.…”
Section: Two Years Of Covid-19 In the Ms Communitymentioning
confidence: 99%
See 4 more Smart Citations
“…As MS is an immune-mediated disease and DMTs alter or suppress the immune system in different ways, many recent studies have focused on the immunological responses after SARS-CoV-2 infection or vaccination. Overall, most pwMS present an immunological response after SARS-CoV-2 infection (humoral response: 76.8%-83.4%; cellular response: 59.5%) [11][12][13] or vaccination (humoral response: 74.4%-86.8%; cellular response: 62%-84.4%) [14][15][16][17] regardless of their treatment. However, it is clear by now that anti-CD20 therapies and sphingosine-1-phosphate receptor modulator (SP1RM) therapies decrease these responses.…”
Section: Two Years Of Covid-19 In the Ms Communitymentioning
confidence: 99%
“…However, it is clear by now that anti-CD20 therapies and sphingosine-1-phosphate receptor modulator (SP1RM) therapies decrease these responses. 11,[15][16][17][18] Anti-CD20 therapies impair memory B-cell production, leading to a blunted humoral response. In the study of Sormani et al, an SARS-CoV-2 serological response, after COVID-19, was observed in only 44.6% of patients on anti-CD20 therapies compared with 78.7% of the rest of patients.…”
Section: Two Years Of Covid-19 In the Ms Communitymentioning
confidence: 99%
See 3 more Smart Citations